DEVELOPING THE LEARNING MATERIALS OF READING 2 INTEGRATED WITH ISLAMIC VALUES - Amirudin Latif (Premise: Journal of English Education and Applied Linguistics, 2016)
The objective of the study is to develop the learning materials of reading 2 integrated with Islamic values. The design of the study is research and development (R&D). The setting of the study is English Education Department of Teacher Training and Education Faculty of Muhammadiyah University of Metro. The respondents of study are lecturer and students of the third semester. The steps of the study are need analysis, the result of need analysis, material development, expert validation, try out, and final product. The result of the study is materials of reading 2 inserted with Islamic values. The materials are compiled in a book which consists of five units. Each unit consists of text material, example of texts, vocabulary, and exercises.